EVOLUTIONARY EVIDENCE FOR THE PREVALENCE OF TY3 GYPSY SUBCLASS RETROTRANSPOSONS DURING ANNOTATION OF GERANIOL DEHYDROGENASE GENE IN JAVA CITRONELLA (CYMBOPOGON WINTERIANUS JOWITT) - AAKANKSHA WANY; VINOD KUMAR NIGAM; DEV MANI PANDEY (International Journal of Pharma and Bio Sciences, 2015)
When GDH- specific amplified product was annotated after three times of sequencing, it showed the similarity with Ty3 gypsy class retrotransposon protein of O. sativa, Z. mays and S. bicolor. Annotation was confirmed by the phylogenetic analysis performed between the new and LTR-RT sequences of the model plants. It was confirmed that C. winterianus have been evolved from Z. mays around 22.85 mya and thus, only a small subset of LTR sequence (6%) is showing similarity with Z. mays as compared to the 1083 bp GDH sequence. A new 1536 bp with gene coordinates <1…714, 730…909, 949…1407, 1426…1536> Ty3-gyspy class of RT containing mobile element sequence spanning from 1186-1536 bp with GenBank accession no. KF415292 in NCBI as Cymbopogon winterianus RT sequence was released. Thus, there may a prevalence of LTR-RT’s across the Citronella genome as evidenced by the evolutionary history of Citronella being distantly related to wild Z. mays.